Dynamic behavior of clusters in the early stage of SiC (0001) epitaxial growth: A Kinetic Monte Carlo study. (June 2021) - Chen, Xuejiang; Ai, Wensen; Zhao, Hao; Li, Yuan; Feng, Jianmei
Abstract: A Kinetic Monte Carlo (KMC) model with a cluster-multiple labeling technique was proposed to study the effect of growth parameters such as temperature, deposition flux and Si/C ratio on Si–C clusters in the initial stage of SiC (0001) surface nucleation. In this model, Si and C atoms were treated individually and a crystal lattice was established to fix the physical location of atoms and interatomic bonding. The adsorption and diffusion of adatoms on the planar surface, attachment to and detachment from clusters of adatoms, and their diffusion along the edge of clusters were considered in the KMC model. Cluster-multiple labeling technique was used to identify Si–C clusters and the properties of clusters were analyzed. The results showed that larger and less clusters were constructed on growing surface with the increase of temperature and decrease of deposition rate. The saturated clusters density was exponentially related to the ratio of effective diffusion capacity to deposition rate, and the relationship between saturated density of clusters and average growth rate of clusters was obtained. Finally, Si/C ratio affected the characteristics of nucleation, and at C-rich condition, the binding energy of nucleus was larger than that at Si-rich condition, leading to the formation of fewer but larger clusters. Highlights: A Kinetic Monte Carlo (KMC) model with Si and C atoms treated individually was proposed. Cluster-multiple labeling technique was used to identify Si–C clusters. Effects of growth condition on Si–C clusters in the initial stage of SiC (0001) surface nucleation were analyzed.